Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada JNE Cabang Bandung [The Influence of Service Quality on Customer Satisfaction at JNE Branch in Bandung] - Januar Efendi Panjaitan; Ai Lili Yuliati (Universitas Pelita Harapan, 2016)
The purpose of this study was to determine the effect of Quality of Service Quality of Service Customer Satisfaction either simultaneously or partially on Cabang JNE Bandung. JNE is a freight company and documents that have been established since 1990. In 2004, JNE set up headquarters in Jakarta. The JNE Bandung has a branch office in Jalan Permata Kawaluyaan numbers 1-4 Soekarno Hatta, Bandung. The type of research used in this study was descriptive research type using a quantitative approach. The analysis technique used was descriptive analysis techniques and multiple linear regression. While the sampling technique used was Non Probability sampling using purposive sampling and number of samples of 78 people. The results of this research showed that the quality of service (X) consisting of Reliability, Assurance, Tangibles, Empathy, and Responsiveness simultaneously had significant influence on satisfaction of customers with significant value (p value) of 0.003 < 0.05. Partial test results showed that the only variable that empathy has a partial effect on was customer satisfaction with the number of variables of significance (p value) amounted to 0.021 < 0.05.